STUDY OF PRODUCTION AND VIABILITY COCOON OF Pontoscolex corethrurus FR.MULL AT VARIOUS CONCENTRATIONS OF CARBARYL INSECTICIDES - Nofyan, Erwin; Kamal, Mustafa; Lamin, Syafrina; Rahmasari, Nafira Putri (BIOVALENTIA: Biological Research Journal, 2019)
Research on the Study of Cocoon Production and Viability of Pontoscolex corethrurus Fr. Mull at various concentrations of Karbaril insecticide was carried out in July to October 2019, at the Laboratory of Animal Physiology, Department of Biology, Faculty of Mathematics and Natural Sciences, Sriwijaya University, Inderalaya, Ogan Ilir, South Sumatra. This study aims to study the production of cocoon and viabiltas earthworm Pontoscolex corethrurus Fr. Mull at various concentrations of carbaryl insecticide as well as getting concentrations of carbaryl insecticide began to react to the amount of cocoon and viability of the earthworm Pontoscolex corethrurus Fr.Mull. Contribution of research on the availability of data on the production of cocoon and viabiltas cocoon of earthworm Pontoscolex corethrurus Fr.Mull after being given various concentrations of carboxyl insecticide and providing information especially to farmers about the effect of various concentrations of carbaryl insecticide on non-target animals, especially soil animals namely Pontoscolex corethrurus Frethrurus earthworm . Mull. This study uses a completely randomized design with 6 (six) treatments and 5 (five) repetitions. The treatment given in the form of carboxyl insecticide with a concentration of 0% (control); 0.1%; 0.2%; 0.3%; 0.4%; 0.5%. Data were analyzed by Analysis of Variance, if there were significant differences followed by Duncan's Test at a 95% confidence level. The results showed that the treatment of various concentrations of carboxyl insecticide significantly affected the average number of cocoon and viability of the earthworm cocoon Pontoscolex corethrurus Fr. Mull. Average number of earthworm cocoons Pontoscolex corethrurus Fr. The lowest Mull was found in the administration of carboxyl insecticide at a concentration of 0.5%, 0.62 ± 0.06 cocoon / individual / week and the average number of earthworm cocoons Pontoscolex corethrurus Fr. The highest Mull was found in the administration of carboxyl insecticide at a concentration of 0% (control), namely 3.62 ± 0.02 cocoon / individual / week. The average viabiltas cocoon of earthworms Pontoscolex corethrurus Fr. The lowest Mull was found in the administration of carboxyl insecticide at a concentration of 0.5%, namely 18.85 ± 1.19% and the average viability of the earthworm cocoon Pontoscolex corethrurus Fr. The highest Mull was found in the administration of carboxyl insecticide at a concentration of 0%, namely 98.65 ± 2.15%